Preparation of Agricultural Jiaosu from vegetable waste: multi-dimensional effects of microbial inoculants on the properties of Agricultural Jiaosu and fertilizer efficiency - Chen, Zhuo; Liu, Xiaocui; Ban, Tiantian; Ma, Chao (Frontiers in Microbiology, 2025)
Purpose of the study: To explore the effects of adding different bacterial agents before fermentation on the Agricultural Jiaosu derived from waste from Chinese cabbage.Material and methods: This study used the waste from Chinese cabbage as the raw material and added Lactobacillus, Acetobacter, Yeast, and Bacillus subtilis respectively for fermentation treatment. Systematic research was conducted on the effects of different bacterial agents on the nutritional elements, microbial diversity, organic acid content of Agricultural Jiaosu, as well as their impacts on the growth and yield of Chinese cabbage.Results: The results showed that there were significant differences in the above aspects among the treatments with different bacterial agents. In terms of nutritional elements, the treatment group with Lactobacillus addition had the highest total carbon, total nitrogen, and total phosphorus contents; the treatment group with Acetobacter addition had the highest total potassium and carbon-nitrogen ratio. Microbial diversity analysis revealed that the relative abundance of Bacteroides was higher in the Lactobacillus treatment group; Arcobacter and Vishniacozyma were relatively more abundant in the Acetobacter and Bacillus subtilis treatment groups; and the relative abundance of Lysinibacillus was higher in the Yeast treatment group. Organic acid content analysis indicated that the benzoic acid content was higher in the Lactobacillus treatment group; the benzenepropanoic acid, azelaic acid, and pyroglutamic acid contents were higher in the Acetobacter treatment group; the succinic acid content was the highest in the Yeast treatment group; and the glutaric acid content was the highest in the Bacillus subtilis treatment group. Moreover, the effects of the Yeast and Acetobacter treatment groups on promoting the growth of Chinese cabbage were more significant.Conclusion and future prospective: In conclusion, Agricultural Jiaosu is rich in abundant nutritional elements, diverse microbial communities, and various organic acids, and has a significant fertilizer effect on Chinese cabbage production. Adding different bacterial agents before fermentation leads to differences in the composition and function of the finished Agricultural Jiaosu products. Therefore, appropriate bacterial agents can be selected for fermentation according to specific application goals to optimize the performance and application effect of Agricultural Jiaosu.